2018
DOI: 10.1111/febs.14594
|View full text |Cite
|
Sign up to set email alerts
|

Claspin – checkpoint adaptor and DNA replication factor

Abstract: Claspin was discovered as a Chk1-interacting protein necessary for Chk1 phosphorylation and activation by the upstream kinase, ATR, in response to DNA synthesis inhibition in Xenopus oocyte extracts. Subsequent investigations have defined a molecular model in which Claspin acts as an adaptor or scaffold protein to facilitate activation of Chk1 by ATR within a multiprotein complex that forms on single-stranded DNA at stalled replication forks and sites of DNA damage. Interestingly, Claspin is an unstable protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 76 publications
(62 citation statements)
references
References 73 publications
(147 reference statements)
0
62
0
Order By: Relevance
“…Cell fractionation showed that OZF is a chromatin‐bound protein (Figure 3A). To investigate if this chromatin‐bound OZF interacts, similarly to Claspin, with replisome proteins, 18 immunoprecipitation of chromatin‐bound OZF was performed. As shown in Figure 3B, OZF from nuclear extract co‐immunoprecipitated not only with Claspin (Figure 1), but also with Cdc45, MCM6, and MCM2, components of the CMG complex.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell fractionation showed that OZF is a chromatin‐bound protein (Figure 3A). To investigate if this chromatin‐bound OZF interacts, similarly to Claspin, with replisome proteins, 18 immunoprecipitation of chromatin‐bound OZF was performed. As shown in Figure 3B, OZF from nuclear extract co‐immunoprecipitated not only with Claspin (Figure 1), but also with Cdc45, MCM6, and MCM2, components of the CMG complex.…”
Section: Resultsmentioning
confidence: 99%
“…We first identified OZF as a Claspin‐binding protein by a two‐hybrid analysis and the interaction was also confirmed by co‐immunoprecipitation with both exogenously expressed proteins and endogenous proteins. Claspin is a protein that interacts with several replisome components and travels with this protein complex in active replication forks while DNA is synthesized 18,22 . Thus, to examine whether OZF was also present in these structures, the interaction of OZF with replisome components was analyzed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While it is currently unknown whether mammalian ATR directly phosphorylates Claspin, Xenopus ATR has been shown to directly phosphorylate Claspin at threonines 817 and 819, which are critical for CHK1 recruitment (Fig 2; the uncertainty of ATR's direct phosphorylation of Claspin in humans is denoted by "? "; Yoo et al, 2006; in-depth discussion of the similarities and differences between Claspin orthologs can be found here: Smits et al, 2019). Once bound to CHK1, Claspin is thought to both stabilize CHK1 and tether it in proximity to ATR, allowing for extensive phosphorylation and full activation of the effector kinase (Liu et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Bertolli et al, have shown that oncogenic stimulation causes replication stress, and oppositely, sustained E2F-dependent transcription allows the cells to decrease replicative stress and remove the block for cell proliferation [63]. During oncogenic transformation, cells could utilize claspin, because it helps to circumvent replicative stress [64]. However, in this study, we have shown that an increase in c-Myc and possibly E2F transcription factors are decisive factors in aiding enhanced cell proliferation due to IHH stimulus.…”
Section: Discussionmentioning
confidence: 50%